Comparative analyses of regulatory T cell subsets in patients with hepatocellular carcinoma: A crucial role of CD25 super(-)FOXP3 super(-) T cells - Kakita, Naruyasu; Kanto, Tatsuya; Itose, Ichiyo; Kuroda, Shoko; Inoue, Michiyo; Matsubara, Tokuhiro; Higashitani, Koyo; Miyazaki, Masanori; Sakakibara, Mitsuru; Hiramatsu, Naoki; Takehara, Tetsuo; Kasahara, Akinori; et al. (International journal of cancer, 2012)
Regulatory T cells (Tregs) play pivotal role in cancer-induced immunoediting. Increment of CD25 super(high+)FOXP3 super(+) natural Tregs has been reported in patients with hepatocellular carcinoma (HCC); however, the involvement of other type of Tregs remain elusive. We aimed to clarify whether FOXP3 super(-) Tregs are increased and functionally suppressive or not in patients with HCC. We enrolled 184 hepatitis C-infected patients with chronic liver diseases or HCC, 57 healthy subjects and 27 HCC patients with other etiology. Distinct Treg subsets were phenotypically identified by the expression of CD4, CD25, CD127 and forkhead/winged helix transcription factor (FOXP3). Their gene profiles, frequency and suppressor functions against T cell proliferation were compared among the subjects. To examine the molecules involving in Treg differentiation, we cultured naive CD4 super(+) T cells in the presence of HCC cells and dendritic cells. We determined two types of CD4 super(+)CD127 super(-) T cells with comparable regulatory ability; one is CD25 super(high+) cells expressing FOXP3 (CD25 super(high+)FOXP3 super(+) Tregs) and the other is CD25 super(-) cells without FOXP3 super(-) expression (CD25 super(-)FOXP3 super(-) cells). The peripheral or intrahepatic frequency of CD25 super(-)FOXP3 super(-) Tregs in HCC patients is higher than those in other groups, of which significance is more than CD25 super(high+)FOXP3 super(+) cells. Of importance, CD25 super(-)FOXP3 super(-) Tregs, but not CD25 super(high+)FOXP3 super(+) cells, dynamically change in patients accompanied by the ablation or the recurrence of HCC. CD25 super(-)FOXP3 super(-) T cells with CD127 super(-)IL-10 super(+) phenotype are inducible in vitro from naive CD4 super(+) T cells, in which programmed cell death 1 ligand 1, immunoglobulin-like transcript 4 and human leukocyte antigen G are involved.. In conclusion, CD25 super(-)FOXP3 super(-) Tregs with suppressive capacity are increased in patients with HCC, suggesting their distinct roles from CD25 super(+)FOXP3 super(+) Tregs.